Abundance of eastern North Pacific gray whales on the 1995/96 southbound migration - Hobbs , R. C.; Rugh, D. J.; Waite, J. M.; Breiwick, J. M.; DeMaster, D. P. (J. Cetacean Res. Manage., 2023)
Systematic counts of gray whales (Eschrichtius robustus) were conducted from 13 December 1995 to 23 February 1996 at Granite Canyon, California. This study was the second of three during the five-year period following the removal of gray whales from the US government list of endangered and threatened wildlife. The counts were made at the same research station used most years since 1975 by the National Marine Mammal Laboratory to observe the southbound migration of the eastern North Pacific stock. Counting methods were kept similar to those used in previous surveys and included double counting to assess observer performance. In addition, aerial surveys and highpowered binoculars provided documentation that a negligible fraction of migrating whales passed beyond the sighting range of the counting observers. A total of 2,151 pods (3,928 whales) was counted during 472.7hrs of standard watch effort with visibility recorded as fair to excellent. Data analysis procedures were substantially the same as in previous years with a modification to account for differential sightability by pod size. Population size is estimated to be 22,263 whales (CV=9.25%; 95% log-normal CI=18,700-26,500). This estimate is similar to the previous estimate of 23,109 (CV=5.42%; 95% CI=20,800-25,700) from the 1993/94 survey.